Preliminary Validation of the Learning Ratio for the HVLT–R and BVMT–R in Older Adults. Issue 3 (September 2021) - Hammers, Dustin B.; Gradwohl, Brian D.; Kucera, Amanda; Abildskov, Tracy J.; Wilde, Elisabeth A.; Spencer, Robert J.
Abstract : Background: The learning slope is typically represented as the raw difference between the final score and the score of the first learning trial. A new method for calculating the learning slope, the learning ratio (LR), was recently developed; it is typically represented as the number of items that are learned after the first trial divided by the number of items that are yet to be learned. Objective: To evaluate the convergent and criterion validity of the LR in order to understand its sensitivity to Alzheimer disease (AD) pathology. Method: Fifty-six patients from a memory clinic underwent standard neuropsychological assessment and quantitative brain imaging. LR scores were calculated from the Hopkins Verbal Learning Test—Revised and the Brief Visuospatial Memory Test—Revised and were compared with both standard memory measures and total hippocampal volumes, as well as between individuals with AD and those with mild cognitive impairment. Results: Lower LR scores were consistently associated with poorer performances on standard memory measures and smaller total hippocampal volumes, generally more so than traditional learning slope scores. The LR scores of the AD group were smaller than those of the group with mild cognitive impairment. Furthermore, the aggregation of LR scores into a single metric was partially supported. Conclusion: The LR is sensitive to AD pathology along the AD continuum. This result supports previous claims that the LR score can reflect learning capacity better than traditional learning calculations can by considering the amount of information that is learned at trial 1.